High carrier mobility and ultralow thermal conductivity in the synthetic layered superlattice Sn4Bi10Se19. Issue 7 (12th March 2021) - Lu, Ruiming; Olvera, Alan; Bailey, Trevor P.; Fu, Jiefei; Su, Xianli; Veremchuk, Igor; Yin, Zhixiong; Buchanan, Brandon; Uher, Ctirad; Tang, Xinfeng; Grin, Yuri; Poudeu, Pierre F. P.
Abstract : Phonon scattering from Bi2 Se3 /SnSe/Bi2 Se3 interfaces and high carrier mobility within the 2D Bi2 Se3 -layer lead to the coexistence of ultralow lattice thermal conductivity and high electrical conductivity in the Sn4 Bi10 Se19 synthetic superlattice. Abstract : The integration within the same crystal lattice of two or more structurally and chemically distinct building units enables the design of complex materials featuring the coexistence of dissimilar functionalities. Here we report the successful synthesis of single-phase polycrystalline powder of Sn4 Bi10 Se19, a ternary selenide featuring atomic-scale integration of SnSe-type and Bi2 Se3 -type building blocks into a large monoclinic unit cell. We found that the complex layered atomic structure along with the large size of the building blocks severely impede the crystallization of an ordered phase. Consequently, the electronic and thermal transport properties of Sn4 Bi10 Se19 are strongly influenced by the degree of crystallinity and atomic ordering within the crystal lattice. At temperatures below 300 K, the well-crystallized Sn4 Bi10 Se19 sample displays higher carrier density, carrier mobility, and electrical conductivity compared to the poorly crystallized sample, while both samples show similar electronic properties at high temperatures. Astonishingly, the crystalline sample exhibits up to 30% lower thermal conductivity at 535 K compared to the poorly crystallized sample. This suggests a more efficient phonon scattering at the ordered atomic-scale interfaces between the building blocks in the crystalline sample, owing to bond inhomogeneity and anisotropy, whereas the random orientation of building blocks in the poorly crystallized sample inhibits such effect.